Research on interaction of controllable series compensation and traditional PSS to suppress low-frequency oscillation - Li, Ming; Ren, Wenbo; Chen, Anqing; Gong, Jiayuan; Wang, Jingnan (Frontiers in Energy Research, 2023)
In order to make power transportation more stable, ensure the safety of system operation, and prevent major accidents, a research on the interaction of controllable series compensation and traditional PSS to suppress low-frequency oscillation is proposed. Use PSS to limit the stabilizer, adjust the lead-slip angle of the stabilizer through the lead-lag module, eliminate the reverse modulation phenomenon, optimize the power flow of parallel transmission lines and lines with different voltage levels by using series compensation, and improve the transmission capacity and system of long-distance transmission systems. Stability; the parameters of the TCSC and PSS damping controllers are set by the phase compensation method, the damping ratio is used to judge the damping characteristics of the rotor system, the sensitivity characteristic root is extracted, and the parameters that have the greatest influence on the mode are determined; based on the genetic algorithm, the damping controller is coordinated, Increase the damping of the oscillation mode, constrain the range of each parameter to be tuned, and complete the coordinated optimization. Through experiments, it is proved that the method in this paper can effectively suppress the low frequency oscillation and ensure the safety and stability of the power system.